The tale tradition of art in the folklore of Turkic peoples - Мусaгуловa, Г. Ж. (Journal of Oriental Studies, 2017)
The article of has given the formation about tale art in the folklore of the Turkic peoples. She presented the main publications, rich ethnographic materials of Turkic folklore in scientific journals, collections of translations supplied with necessary comments necessary comments, first appeared in the last quarter of 19th century in the beginning of the 20th century, as well as in the 21st century, which showed capital study of the large-scale industry. The author conducts a historical excursion into tale art and gives the names of prominent personalities from various Turkic peoples. Author traces the development of the tradition of storytelling, so prevalence within the musical folklore of the peoples of the Turkic khanate, presenting it as the most contemporary direction.